Analysis of Factors Affecting Purchasing Decisions (Study on Garlic MSMEs in Pare Kediri)) - Novilia, Evita; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to examine how customers in Pare Kediri make purchasing choices for garlic MSMEs in relation to pricing, promotion, and product quality. The data was collected quantitatively using questionnaires and 120 participants. The significance of an integrated marketing strategy is shown by the study findings, which demonstrate that the three factors have a positive and substantial impact on purchase choices. The findings provide insights for MSMEs to synergistically manage price, promotion, and product quality to improve competitiveness and consumer satisfaction. This study also recommends further research to explore other factors influencing purchase decisions and to conduct comparative studies in different regions.